Body mass index and waist circumference of Latin American adult athletes with intellectual disability - John T Foley; Meghann Lloyd; Lesley Turner; Viviene A Temple (Instituto Nacional de Salud Pública, 2017)
Objectives. To examine both body mass index (BMI) status and waist circunference (WC) in a large international sample of adult Special Olympics participants from Latin America. It also explored the association of age and sex with obesity in this population. Materials and methods. BMI and WC records from a total of 4 174 (2 683 male and 1 491 female) participant records from the Special Olympics International Health Promotion database were examined. Results. The prevalence of overweight and obesity was quite high (i.e. >40%), but generally lower than studies involving adults with intellectual disabilities from Europe and the USA. Chi-square analyses revealed that both increasing age and being female significantly predicted levels of overweight, obesity, and WC. Conclusions. These results suggest that efforts need to be made to prevent and reduce rates of overweight and obesity among Latin American Special Olympics participants,particularly women.